2017
DOI: 10.1093/arclin/acx112
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Neuropsychiatric Correlates of Functional Impairment Across the Continuum of No Cognitive Impairment to Dementia

Abstract: The implications for developing cognitive rehabilitation interventions are discussed, with a recommendation for interventions for symptoms of apathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…Apathy manifests as a lack of motivation and interest, taking initiative, and goal-directed behavior. This may negatively influence a person’s ability to take initiative in participating in social contact with others, to perform self-care activities, as well as to find things to do without help from others [45]. Depressive symptoms were associated with a worse care relationship, lower positive affect, lower positive self-image, more negative affect, and more restless tense behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Apathy manifests as a lack of motivation and interest, taking initiative, and goal-directed behavior. This may negatively influence a person’s ability to take initiative in participating in social contact with others, to perform self-care activities, as well as to find things to do without help from others [45]. Depressive symptoms were associated with a worse care relationship, lower positive affect, lower positive self-image, more negative affect, and more restless tense behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Stroop test is used in exercise trials in these patient groups [ 18 , 19 , 20 , 21 ]. However, patients with dementia may have difficulty understanding and executing the task [ 22 ], which should be taken into account in the interpretation of the Stroop results. Furthermore, it should be noted that we assessed Flanker performance in subjects who participated in an exercise or control program for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sleep disorders (nocturnal wakefulness) in AD patients were highly associated with anxiety levels (OR2.1) and ADL disorder (OR1.6) [ 12 ]. Apathy for normal and MCI participants was moderately associated with IADL [ 25 ]. Vascular dementia (VaD) patients’ level of apathy has also been reported as a predictor of BADL/IADL performance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that IADL independence declines and BPSD (apathy, depression) emerge from the MCI stage, and the association between the two has already been confirmed [ 23 , 24 , 25 ]. Additionally, studies have highlighted that MCI can lead to BPSD and a decline in IADL [ 14 , 25 ]. For example, it has also been shown that apathy is a predictor of complex ADL, especially in mild AD with a clinical dementia rating = 0.5 [ 26 ].…”
Section: Introductionmentioning
confidence: 93%